RI 3307 Ventilation of Manholes I. - Effect of Hole Covers on Natural Ventilation - G. W. Jones; W. E. Miller; John Campbell; W. P. Yant (The National Institute for Occupational Safety and Health (NIOSH), 1936)
"Because of its interest in accident prevention, the U.S. Bureau of Mines cooperates with city officials and utilities in investigating the causes of explosions in sewers, manholes, and other underground openings and in developing means for preventing such explosions. For several years this Bureau has been cooperating with the Edison Electric Illuminating Co. of Boston and the Boston Consolidated Gas Co. in detecting and eliminating combustibles and physiologically harmful gases in manholes in the city of Boston and adjacent territory.These Bureau of Mines investigations° have shown that combustible gases from the usual sources — leakage from gas—distributing systems and from underground tanks and gasoline wastes — can be located and the dangerous conditions remedied by a well—planned, adequately supervised, systematic, and continuous manhole survey. However, other types of gas, which are termed here ""soil"" gases, also occur in manholes and are more difficult to eliminate because they have no fixed origin and because seasonal and barometric changes affect their production and passage into the manhole space. These gases appear to be produced by bacterial and fermentation or through reactions of entrapped air in the soil. Soil usually abnormally high in carbon dioxide and low in oxygen, and contain varying amounts of methane. They are especially clangorous to men entering manholes because they lack sufficient oxygen to support life. Owing to the difficulty of constructing gastight manholes the most feasible method for eliminating soil gases from manholes is by ventilation. Consequently the Bureau of Mines initiate 4 study of natural ventilation methods for the removal of these gases from manholes and also for taking care of unforeseen accumulations of combustible gases and vapors.The following factors were considered by the Bureau to be important to the natural ventilation of manholes: (1) Relation of area of ventilation opening* to the capacity of the manholes, (2) size and shape of the manhole, (3) design of the ventilation opening (4) and velocity, and (5) weather conditions."